Ball-in-ball ZrO2 nanostructure for simultaneous CT imaging and highly efficient synergic microwave ablation and tri-stimuli-responsive chemotherapy of tumors. Issue 25 (20th June 2017) - Long, Dan; Niu, Meng; Tan, Longfei; Fu, Changhui; Ren, Xiangling; Xu, Ke; Zhong, Hongshan; Wang, Jingzhuo; Li, Laifeng; Meng, Xianwei
Abstract : A novel ball-in-ball hollow ZrO2 structure with high microwave energy conversion rate was designed for synergic microwave ablation and chemotherapy. Abstract : Combined thermo-chemotherapy displays outstanding synergically therapeutic efficiency when compared with standalone thermotherapy and chemotherapy. Herein, we developed a smart tri-stimuli-responsive drug delivery system involving X@BB-ZrO2 NPs (X represents loaded IL, DOX, keratin and tetradecanol) based on novel ball-in-ball-structured ZrO2 nanoparticles (BB-ZrO2 NPs). The microwave energy conversion efficiency of BB-ZrO2 NPs was 41.2% higher than that of traditional single-layer NPs due to the cooperative action of self-reflection and spatial confinement effect of the special two-layer hollow nanostructure. The tri-stimuli-responsive controlled release strategy indicate that integrated pH, redox and microwaves in single NPs based on keratin and tetradecanol could effectively enhance the specific controlled release of DOX. The release of DOX was only 8.1% in PBS with pH = 7.2 and GSH = 20 μM. However, the release could reach about 50% at the tumor site (pH = 5.5, GSH = 13 mM) under microwave ablation. The as-made X@BB-ZrO2 NPs exhibited perfect synergic therapy effect of chemotherapy and microwave ablation both in subcutaneous tumors (H22 tumor-bearing mice) and deep tumors (liver transplantation VX2 tumor-bearing rabbit model). There was no recurrence and death in the X@BB-ZrO2 + MW group during the therapy of subcutaneous tumors even on the 42 nd day. The growth rates in the deep tumor of the control, MW and X@BB-ZrO2 + MW groups were 290.1%, 14.1% and −42% 6 days after ablation, respectively. Dual-source CT was used to monitor the metabolism behavior of the as-made BB-ZrO2 NPs and traditional CT was utilized to monitor the tumor growth in rabbits. Frozen section examination and ICP results indicated the precise control of drug delivery and enhanced cytotoxicity by the tri-stimuli-responsive controlled release strategy. The ball-in-ball ZrO2 NPs with high microwave energy conversion efficiency were first developed for synergic microwave ablation and tri-stimuli-responsive chemotherapy, which may have potential applications in clinic.